2017
DOI: 10.1098/rstb.2016.0291
|View full text |Cite
|
Sign up to set email alerts
|

And yet, it moves: nuclear and chromatin dynamics of a heterochromatic double-strand break

Abstract: Heterochromatin is mostly composed of repeated DNA sequences prone to aberrant recombination. How cells maintain the stability of these sequences during double-strand break (DSB) repair has been a long-standing mystery. Studies in Drosophila cells revealed that faithful homologous recombination repair of heterochromatic DSBs relies on the striking relocalization of repair sites to the nuclear periphery before Rad51 recruitment and repair progression. Here, we summarize our current understanding of this respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 182 publications
(474 reference statements)
2
69
0
Order By: Relevance
“…Relocalization of heterochromatic DSBs and expansion of the domain also occurs in mouse cells [2,11,16,28,29], suggesting conserved pathways [26,27]. However, in mouse cells, heterochromatic DSBs do not appear to reach the nuclear periphery and repair sites are detected at the periphery of DAPI-bright regions, where Rad51 is recruited [2,11,16,29].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Relocalization of heterochromatic DSBs and expansion of the domain also occurs in mouse cells [2,11,16,28,29], suggesting conserved pathways [26,27]. However, in mouse cells, heterochromatic DSBs do not appear to reach the nuclear periphery and repair sites are detected at the periphery of DAPI-bright regions, where Rad51 is recruited [2,11,16,29].…”
Section: Introductionmentioning
confidence: 98%
“…Inactivating the relocalization pathway results in aberrant recombination and widespread genomic instability [10,11,13,20], revealing its importance to genome integrity. Relocalization likely promotes 'safe' HR repair while preventing aberrant recombination, by isolating DSBs and their repair templates (on the homologous chromosome or the sister chromatid) away from nonallelic (ectopic) sequences before strand invasion [10,11,13,20] (reviewed in [2,26,27]). Notably, Drosophila homologous chromosomes are paired in interphase, thus both sister chromatids and homologous chromosomes are readily available for DSB repair.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest highly conserved strategies for 'safe' heterochromatin repair. Relocalization likely prevents ectopic recombination by isolating the damaged site and its homologous sequences (on the homologous chromosome or the sister chromatid) away from similar sequences on ectopic chromosomes, before strand invasion (Amaral et al, 2017;P. C. Caridi et al, 2017;Chiolo et al, 2011;Chiolo et al, 2013;Ryu et al, 2016;Ryu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a major body of work in yeast and mammalian cells revealed the dynamic nature of chromatin in both damaged and undamaged regions (reviewed in (Amaral et al, 2017;P. C. Caridi et al, 2017)).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that, at least in late S/G2 phase, HR is exploited to repair DSBs within transcriptionally active regions, a possibility that appears rational given the potential enhanced accuracy of HR compared with NHEJ [44]. As discussed in the review by Chiolo and colleagues [30], there is also evidence, though with less obvious rationality, that DSBs within repeat sequences may be preferably repaired by HR. If correct, then what determines how the optimal pathway is chosen and how do these signals interface with damage-induced chromatin modifications?…”
mentioning
confidence: 99%